Study of dense granule proteins in Eimeria spp. identifies a limited repertoire with potential as vaccine candidates - Sanchez-Arsuaga, Gonzalo; Blake, Damer P.; Tomley, Fiona M.; Marugan-Hernandez, Virginia (Frontiers in Immunology, 2025)
Eimeria species are obligate intracellular parasites that usually replicate in intestinal cells and can cause the disease coccidiosis. Coccidiosis of livestock and poultry incurs significant production losses and compromises animal welfare, with the greatest impact occurring in chicken production. Control of coccidiosis is challenging, requiring good husbandry and effective drug or live vaccine prophylaxis, and there is demand for more scalable and cost-effective vaccines. Proteins secreted from dense granules (GRAs) play crucial roles in intracellular survival in many apicomplexans, but knowledge of these organelles and their secreted proteins in Eimeria is extremely limited. In this study, we observed a reduced GRA protein repertoire encoded in Eimeria spp. genomes compared to Toxoplasma gondii (23 vs. 71) with just 12 orthologues identified in the Eimeria tenella genome. In silico analysis of three of these putative dense granule proteins - EtGRA9, EtGRA12a, and EtGRA12b - revealed the presence of signal peptides in EtGRA9 and EtGRA12b, while none was detected in EtGRA12a. Sequence analysis of E. tenella field isolates revealed a limited number of polymorphisms in the genes encoding these three proteins, suggesting purifying selection possibly related to their functional importance. In contrast, E. maxima showed greater variation, indicating relaxed selective pressure or diversifying selection. When expressed as recombinant proteins all three were recognised by sera from chickens previously infected with E. tenella. Their potential role in parasite intracellular niche formation and close interaction with the host cell makes them promising antigens for vaccine development. To evaluate this potential, EtGRA9 was expressed as a recombinant protein and used to vaccinate chickens prior to E. tenella challenge. Immunisation with recombinant EtGRA9 reduced parasite load in the caeca by 85.7%, comparable to immunisation with recombinant EtAMA1, an antigen previously shown to confer significant protection.